Morphological and structural transformations of indium oxide nanostructures in ammonia growth ambient by atmospheric chemical vapor deposition. (1st November 2020) - Aper, T.M.; Yam, F.K.; Poay, Beh Khi; Jubu, P.R.
Abstract: In this paper, we present a comparative study of the growth of indium oxide (In2 O3 ) nanostructures on glass substrates by the atmospheric chemical vapor deposition (ACVD) technique in the presence of inert nitrogen and nitrogen/ammonia mixed ambient. Significant differences of the morphological, structural and optical characteristics for the two sets of samples could be observed. The deposited films were examined using FESEM, XRD and UV–vis spectrophotometry respectively. The introduction of ammonia gas in the growth ambient greatly influenced the surface morphology of the produced films, resulting in the formation of structures with well-defined shape as compared to those grown under inert nitrogen environment. XRD analysis show that the change in growth ambient and increase in deposition time have significant effects on the crystal orientation, as crystallite preferential orientation was observed to change from the (400) to (222) plane and vice versa with changes in the growth conditions. Results of the optical analysis show that the prepared films exhibited maximum optical transparency of 65% in the visible region with the optical band gap values ranging from 2.92 to 3.47 eV. Highlights: Two sets of In2 O3 NSs synthesized by ACVD process, under different environments, i.e. inert N2 and N2 /NH3 at 30, 60 and 90 min respectively. The physical properties of In2 O3 NSs grown under inert N2 and N2 /NH3 were found to have significant differences. Change in growth ambient and increase in deposition time can induce the change in preferential crystal growth orientation.